A dimensão axiológica no processo de alfabetização: análise da Base Nacional Comum Curricular à luz de Freire - Lima, Tácyla Agum Theotonio de (2023)
The theme of this study reflects the axiological dimension of the National Common Curricular Basis (NCCB) in the literacy process, in the light of Paulo Freire's pedagogy. This work is the result of a critical analysis of the Portuguese Language subject in the Early Years of Elementary School I, at the NCCB using Freire's critical-liberating pedagogy as an analytical framework. The main objective of the research is to investigate the axiological character of the proximities and distances between the literacy process present in the NCCB and in critical-liberating education. The main objective of the research is to investigate the axiological character of the proximities and distances between the literacy process present in the NCCC and the critical-liberating education. This research presents a qualitative approach using bibliographic research and document analysis. It was necessary to analyze the theoretical-methodological foundation of the NCCB and its curricular structure to understand the conception of education present in this document, to reach the axiological dimension that directs it. In order to perform the documental analysis, we selected the following Freirean categories: reading the articulated words and the world; think right; authentic praxis. The main results of the research are: 1) The conception of the literacy process set out in the NCCB shows a distance from Freire's pedagogy and close proximity to banking education, denounced by Freire; 2) The literacy process proposed in the NCCB presents a reductionist, empiricist and associationist character; and 3) The axiological dimension focused on the literacy process present in the NCCB is based on theoretically and methodologically grounded values in the concept of traditional education.